ANALISIS PENYELESAIAN PERMASALAHAN BOTTLENECK PADA LINI PRODUKSI DI PABRIK TEKSTIL DENGAN METODE KAIZEN - Kurnianingtias, Mayesti; Abdul Rohman Heryadi; Dinarisni Purwanningrum; Galuh Yuli Astrini; Hasna Khairunnisa; Lailin Nur Indah Sari (Jurnal Rekavasi, 2021)
Increasing productivity in the production line is one of the main concerns of PT X in carrying out its activities. PT X is a textile factory that always makes continuous improvements or Kaizen in increasing productivity and reducing the use of resources. This company carries out production activities consisting of pattern making, fabric cutting, fabric grouping, sewing, ironing, and packaging in polybags. With so many processes, line balancing becomes a concern in this study. Cycle time and tact time were calculated in the process of sewing long pants at PT X. The analysis was carried out to determine which part of the production line experienced bottlenecks. The results of the analysis show that there is a bottleneck in the elastic sewing on the waistband process because the cycle time in the process exceeds the tact time. This is due to limited resources in the process. Continuous improvement with the Kaizen method is carried out to reduce cycle time and increase the productivity of the process. Improvements were carried out in 3 stages by simplifying the process, adding tools, replacing machines, and modifying tools. The result shows a decrease in the cycle time of the waistband installation process from 91 seconds to 35 seconds and an increase in productivity from 51 pcs to 103 pcs.